Information Analysis for Medical Expert Systems - Glasziou, P.; Vermeir, D. (Methods of Information in Medicine, 1984)
Much attention has been given to the deductive methods appropriate for medical diagnosis, but much less has been paid to the data structures required to support them. In this paper we apply the linguistically oriented information analysis technique NIAM to the problem and demonstrate how such a conceptual approach could be used for history taking, knowledge acquisition, and diagnosis. We outline the underlying structures in which medical knowledge is traditionally expressed, and use cardiorespiratory disorders as examples. The acyclic network structure of diagnostic categories suggested by this analysis is compared to traditional hierarchical approaches.
Keywords: Information Analysis; Expert Systems; Medical Computing NIAM; Diagnostics